The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0004-282x2002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Taeniasis and cysticercosis prevalence in a small village from Northeastern Brazil

Abstract: Although not considered as an endemic region, the Northeast of Brazil has the necessary conditions for the development of taeniasis-cysticercosis complex. In a previous paper, we demonstrated that Mulungu do Morro municipality, in the State of Bahia, has a high seroprevalence to cysticercosis in epileptic patients. OBJECTIVE: to determine the prevalence of taeniasis and positive cysticercosis serology in the population of Mulungu do Morro. METHOD: blood and stool samples were collected from a random sampling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Other studies have highlighted the importance of identifying the origin of infected herds and tracing of these animals, since it might lead to the identification of high risk areas where the occurrence of taeniasis and cysticercosis would certainly be interrelated (SANTOS, 1993;PARKINSON, 1972;FUKUDA et al, 2003). Although this correlation was not the aim of this study, recent epidemiological data have suggested that some indigenous Brazilian communities (ARAGÃO et al, 2010), and rural villages (GOMES et al, 2002;PRESTES-CARNEIRO et al, 2006). In Brazil beef cattle rearing is primarily done by using the extensive production system where animals have free access to low-land pastures, which might be in direct contact with contaminated streams and rivers.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Other studies have highlighted the importance of identifying the origin of infected herds and tracing of these animals, since it might lead to the identification of high risk areas where the occurrence of taeniasis and cysticercosis would certainly be interrelated (SANTOS, 1993;PARKINSON, 1972;FUKUDA et al, 2003). Although this correlation was not the aim of this study, recent epidemiological data have suggested that some indigenous Brazilian communities (ARAGÃO et al, 2010), and rural villages (GOMES et al, 2002;PRESTES-CARNEIRO et al, 2006). In Brazil beef cattle rearing is primarily done by using the extensive production system where animals have free access to low-land pastures, which might be in direct contact with contaminated streams and rivers.…”
Section: Resultsmentioning
confidence: 84%
“…Additionally, a comparatively higher infection rate below latitude 10º 00' 00'' S, might be the manifestation of reduced population density in areas above this latitude due to the lower concentration of commercial cattle breeding and/or of the reduced human-animal contact. Paradoxically, the northeastern region of Brazil, which is located above this latitude, is endemic for various infectious diseases due to deficient socio-economic conditions which facilitate the transmission and maintenance of the taeniasis/cysticercosis complex (GOMES et al, 2002), but reports of bovine cysticercosis within this region were not found within normal literature databases and were not identified by the SIF. However, porcine cysticercosis due to Taenia solium has been identified in human populations from this region (GOMES et al, 2002;SATO et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The male gender is the most common and the rural area precedence prevails. The predominant clinic manifestation is epilepsy followed by intracranial hypertension [5][6][7][8][9][10][11][12][13] . Cysticerci may be found in an active form causing arachnoiditis, hydrocephaly by meningeal inflammation, parenchymatous cysts and cerebral infarct; or in an inactive form that can be constituted by parenchymatous calcifications.…”
mentioning
confidence: 99%